Post-Pandemic Public Space: How COVID-19 May Permanently Alter the Public Realm - Fisher, Thomas (International Journal of Architectural Engineering Technology, 2023)
This research looks at the impact that pandemics can have on public space. The goal of the research was to learn from the past to anticipate the long-term effects of COVID-19 on the public realm. The research involved exploring the history of the effects of two major global pandemics – the 19th C. Cholera and the 20th C Influenza pandemics – as well as documenting the effects of COVID-19 as they occurred. The main finding of the research is that pandemics have long-lasting impacts on public space, although each has a somewhat different effect, depending upon whether it is bacterial or viral-based and how different countries and cultures respond. The research also shows that COVID-19 has been unique in rebalancing what we do in-person or remotely, physically or digitally, which will likely have profound effects on the use of public as well as private space. This, in turn, will demand a re-evaluation of public policies, many of which are based on pre-pandemic assumptions about in-person interactions as the primary way in which people work, shop, learn, and live.